1999
DOI: 10.1007/s007010050435
|View full text |Cite
|
Sign up to set email alerts
|

Drez Surgery on Conus Medullaris (After Failed Implantation of Vascular Omental Graft) for Treating Chronic Pain due to Spine (Gunshot) Injuries

Abstract: The results of DREZlesioning procedure used for the treatment of chronic intractable pain due to deafferentation caused by gunshot injuries at the thoracolumbar (T10-L1) spine level are reported in six patients. The specificity of these cases arises from the fact that all the patients underwent, after decompressive laminectomy, an implantation of vascularized omental graft on the injured cord segments, 4-17 months after injury. Because of the failure of this method, which did not improve spinal function nor hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 12 publications
0
16
0
3
Order By: Relevance
“…One study conducted a prospective controlled trial, 14 1 utilized a pre-post study design, 9 and 9 studies utilized a case series study design [6][7][8][15][16][17][18][19][20] (see Table 2). In each study, an intervention for pain was administered to an individual with SCI, and the change in pain was measured; only 1 study compared treated individuals with those in a control group.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study conducted a prospective controlled trial, 14 1 utilized a pre-post study design, 9 and 9 studies utilized a case series study design [6][7][8][15][16][17][18][19][20] (see Table 2). In each study, an intervention for pain was administered to an individual with SCI, and the change in pain was measured; only 1 study compared treated individuals with those in a control group.…”
Section: Methodsmentioning
confidence: 99%
“…6,9,19,20 Sindou's technique for MDT involves selectively destroying nociceptive fibers and hyperactive neurons, which interfere with the neurogenic mechanism causing pain. 20 Chun et al 9 reported on 38 individuals treated with the procedure between 2003 and 2008. These individuals had various types of neuropathic pain including segmental versus diffuse, mechanical versus thermal, or a combination of both, and intermittent versus continuous pain.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations